Monitor, Assess, and Act to Optimize Biofiltration. Issue 11 (1st November 2017) - Martin, Barb; Linder, Kevin
Abstract : Biofiltration can provide numerous water treatment benefits but can also pose hydraulic and water quality challenges to operations staff. Carefully monitoring and controlling biofilter conditions are important practices for optimizing a biofiltration plant's performance.